Aseptic Revision and Reoperation Risks After Meniscectomy at the Time of Anterior Cruciate Ligament Reconstruction. Issue 5 (April 2021) - Young, Edmond P.; Chan, Priscilla H.; Prentice, Heather A.; Amar, Karun; Hurvitz, Andrew P.; Khan, Najeeb A.
Background: An intact meniscus is considered a secondary stabilizer of the knee after anterior cruciate ligament reconstruction (ACLR). While loss of the meniscus can increase forces on the anterior cruciate ligament graft after reconstruction, it is unclear whether this increased loading affects the success of the graft after ACLR. Purpose: To identify the risk of subsequent knee surgery when meniscectomy, either partial or total, is performed at the time of index ACLR. Study Design: Cohort study; Level of evidence, 3. Methods: We conducted a matched cohort study using data from the Kaiser Permanente Anterior Cruciate Ligament Reconstruction Registry. Patients were identified who had a primary ACLR performed between January 1, 2005 and December 31, 2016, with up to 12 years of follow-up. The study sample comprised patients with ACLR who had a lateral meniscectomy (n = 2581), medial meniscectomy (n = 1802), or lateral and medial meniscectomies (n = 666). For each meniscectomy subgroup, patients with ACLR alone were matched to patients with a meniscectomy on a number of patient and procedure characteristics. After the application of matching, Cox proportional hazards regression was used to evaluate the risk of aseptic revision, while competing risks regression was used to evaluate the risk of cause-specific ipsilateral reoperation between meniscectomy and ACLR alone. Analysis was performed for each meniscectomy subgroup. Results: After the application of matching, we failed to observe a difference in aseptic revision risk for patients with ACLR and a meniscectomy—lateral (hazard ratio [HR], 0.80; 95% CI, 0.63-1.02), medial (HR, 0.95; 95% CI, 0.70-1.29), or both (HR, 1.25; 95% CI, 0.77-2.04)—as compared with ACLR alone. When compared with patients who had ACLR alone, patients with a lateral meniscectomy had a higher risk for subsequent lateral meniscectomy (HR, 1.89; 95% CI, 1.18-3.02; P = .008), and those with a medial meniscectomy had a lower risk for manipulation under anesthesia (HR, 0.13; 95% CI, 0.02-0.92; P = .041). Conclusion: No difference in aseptic revision risk was observed for patients undergoing primary ACLR between groups with and without meniscectomy at the time of index surgery. Partial lateral meniscectomy at the time of index ACLR did associate with a higher risk of subsequent lateral meniscectomy.